Quality School Management (Study of School Committees, Principal and School Achievement at Cirebon City Public High School) - Agung; Suklani; SIbaweh, Imam (PT Ilmu Inovasi Nusantara, 2023)
Quality provides satisfaction to the user, relative quality provides an illustration of the use of a product that can be used based on satisfaction. Education as the development of quality human resources has the power that can be used for nation development. Reliable quality education contributes to a complete human being. The school committee carries out activities in order to maintain the quality of the school, the principal executes quality activities to make the school quality, the school's achievements cannot be separated from the strength of the committee's resources and the principal who has an active role in every school activity. This research uses a qualitative approach with data collection techniques of observation, document study and interviews. The results of this research really require synergy from all parties, commitment, communication and providing space for discussion and motivating internal school parties and supporting each other.